Financial Literacy in Elementary Schools: A Bibliometric Analysis - Vivin, Meyta; Wiryanto, Wiryanto; Gunansyah, Ganes; Farman, Farman; Syukri, Suhartini (FKIP - Universitas Riau, 2025)
Bibliometric studies on financial literacy have been widely conducted, yet specific attention to elementary school students remains limited. This study aims to explore and identify trends and themes in the literature on financial literacy at the elementary school level from 2010–2024. Data were collected through a search procedure for relevant articles, followed by article selection, metadata completeness checking, and analysis using VOSviewer software. The analysis results show a significant increase in publications since 2016, with the United States and Australia having the most dominant contributions. Carly Sawatzki was recorded as the most productive author, while the most cited article was written by Sherraden et al. Keyword analysis revealed new themes with potential for further research, such as game-based learning, awareness, and culturally relevant pedagogy, began to emerge. These findings provide a comprehensive overview of the development of financial literacy research in elementary schools and identify opportunities and directions for future research in this area.